Synthesis of oxygen containing heterocycles as potential IDO inhibitors - Carvalho, Catarina (2013)
One potentially attractive approach to cancer therapy is to recruit the body’s own immune system to reject solid tumours. The enzyme indoleamine 2,3-dioxygenase (IDO) has been shown to play a major role in supressing immune response, and there is now growing evidence to support the hypothesis that inhibition of IDO produces significant anticancer effects. The development of chemotherapeutic agents for cancer based on the inhibition of indoleamine 2,3-dioxygenase is the purpose of this present work.